Dual-strategy regulation of soil water dynamics: Integrating planting patterns and amendments to mitigate cadmium and arsenic migration in agricultural soils - Jiangdi Deng; Toe Toe Maw; Shihong Tang; Xinran Liang; Wenjin Yan; Bo Li; Yongmei He; Yuan Li; Zuran Li (Ecotoxicology and Environmental Safety)
Cadmium (Cd) and arsenic (As) contamination in agricultural soils has become a critical environmental challenge threatening food security and ecosystem health globally. While soil hydrological processes are recognized as fundamental drivers of Cd and As migration in agricultural soils, the effects of regulating soil water dynamics through agricultural management practices on Cd and As transport remain unclear. We investigated the effectiveness of two remediation strategies in a Cd and As contaminated potato field: (1) planting pattern optimization (PPO), combining intercropping potato with the Sedum plumbizincicola and rotating with ryegrass; and (2) soil amendment (SA), applying biochar and superabsorbent polymer (SAP). The study evaluated the migration patterns of Cd and As under natural rainfall conditions. Cd exhibited higher water distribution coefficients compared to As (P < 0.05), with soil particles migration being the predominant pathway for their losses. PPO effectively reduced the horizontal migration of Cd and As (Cd: 14 %, As: 36 %; P < 0.05) while modifying As vertical distribution patterns between surface (0–20 cm) and subsurface (20–40 cm) soil layers. The combination of PPO and SA showed superior performance, further reducing horizontal migration (47 %) and vertical migration (53 %) of Cd and As (P < 0.05). PPO inhibited the horizontal migration of Cd and As through reducing runoff and soil erosion, while SA inhibited their vertical migration by altering soil water dynamics and bioavailability. These findings indicate that targeted management of soil water dynamics can effectively control Cd and As migration.